ریاست مدینہ اوراسلامی فلاحی مملکت کاتصور ( تعلیمات نبوی ﷺ کی روشنی میں): The concept of an Islamic welfare state within the state of Medina - Dr.Ahmad Raza (Seerat Studies, 2023)
Islam and politics are not separate. If Islam is given a skeleton to politics, it means to demoralize Islam. The basis and survival of the individual is based on three things: society, economy and politics. The basic concept of politics is the state and all political ideas and characters are directly or indirectly related to it. The state of man is a social society which cannot fulfill its natural requirements without any rules and regulations, so it must have a government. The establishment of the Islamic welfare state took place in Madinah during the reign of the Holy Prophet .ﷺ In the Islamic State, the Holy Prophet ﷺ established a clear state system of justice, law, health, industry, education, human rights, trade, defense and foreign affairs, and taught the world how to govern. The Islamic state established by the Holy Prophet ﷺ in Madinah was a welfare state based on revelation and divine teachings. In it, every human being had peace and security and human dignity. Counsel, Equality, Co-operation on Taqwa, Tolerance and Social and Legal Justice were the greatest virtues of this country. This topic is of great importance in this day and age to make Pakistan a truly Islamic welfare state and to make its people proud and prosperous in the world.